Expression patterns of PDGF-A, -B, -C and -D and the PDGF-receptors α and β in activated rat hepatic stellate cells (HSC) - Breitkopf-Heinlein, Katja; Roeyen, Claudia van; Sawitza, Iris; Wickert, Lucia; Floege, Jürgen; Gressner, Axel M. (Cytokine, 2005)
The platelet-derived growth factor (PDGF) family, which regulates many physiological and pathophysiological processes has recently been enlarged by two new members, the isoforms PDGF-C and -D. Little is known about the expression levels of these new members in hepatic fibrosis. We therefore investigated by quantitative real time PCR (Taqman) the mRNA expression profiles of all four PDGF isoforms in transdifferentiating primary cultured hepatic stellate cells (HSC), an in vitro model system of hepatic fibrogenesis, either with or without stimulation of the cells with PDGF-BB or TGF-β1. All four isoforms were expressed in HSC transdifferentiating to myofibroblast-like cells (MFB) albeit with different profiles: while PDGF-A mRNA exhibited minor fluctuations only, PDGF-B was rapidly down-regulated. In contrast, both PDGF-C and -D mRNA were strongly induced: PDGF-C up to 5 fold from day 2 to day 8 and PDGF-D up to 8 fold from day 2 to day 5 of culture. Presence of PDGF-DD in activated HSC was confirmed at the protein level by immunocytochemistry. Stimulation of HSC and MFB with PDGF-BB led to down-regulation of the new isoforms, whereas TGF-β1 upregulated PDGF-A only. We further show that PDGF receptor-β (PDGFR-β) mRNA was rapidly upregulated within the first day of culture and was constantly expressed from day 2 on while the expression profile of PDGFR-α mRNA was very similar to that of PDGF-A during transdifferentiation. Given the dramatic changes in PDGF-C and -D expression, which may compensate for down-regulation of PDGF-B, we hypothesize that the new PDGF isoforms may fulfil specific functions in hepatic fibrogenesis.